Radiation from the impact of broad-line region clouds onto AGN accretion disks - Müller, Ana Laura (2020)
Context. Active galactic nuclei are supermassive black holes surrounded by an accretion disk, two populations of clouds, bipolar jets, and a dusty torus. The clouds move in Keplerian orbits at high velocities. In particular, the broad-line region (BLR) clouds have velocities ranging from 1000 to 10 000 km s-1. Given the extreme proximity of these clouds to the supermassive black hole, frequent collisions with the accretion disk should occur. Aims. The impact of BLR clouds onto the accretion disk can produce strong shock waves where particles might be accelerated. The goal of this work is to investigate the production of relativistic particles, and the associated non-thermal radiation in these events. In particular, we apply the model we develop to the Seyfert galaxy NGC 1068. Methods. We analyze the efficiency of diffusive shock acceleration in the shock of colliding clouds of the BLR with the accretion disk. We calculate the spectral energy distribution of photons generated by the relativistic particles and estimate the number of simultaneous impacts needed to explain the gamma radiation observed by Fermi in Seyfert galaxies. Results. We find that is possible to understand the measured gamma emission in terms of the interaction of clouds with the disk if the hard X-ray emission of the source is at least obscured between 20% and 40%. The total number of clouds contained in the BLR region might be between 3 × 108 and 6 × 108, which are values in good agreement with the observational evidence. The maximum energy achieved by the protons (∼PeV) in this context allows the production of neutrinos in the observing range of IceCube.